On the economy of footballers’ worth. Genius, labour, and other mysteries of recreation - Sedas Nunes, João (2025)
This article examines footballers’ worth as moral economy. For this purpose, it focuses on the two footballers who have dominated world football in the last decade and a half: Lionel Messi and Cristiano Ronaldo. Under the debate over “the best player in the world” both were and are the subject of laudatory and critical discourses that tend to reflect the direct comparison of their qualities and defects. It is through these speeches that we find out that the football singularity articulates the cognitive constraints and the grammatical rules of what pragmatic sociology calls inspiration and industrial cités.